SOS and UVM Pathways Have Lesion-Specific Additive and Competing Effects on Mutation Fixation at Replication-Blocking DNA Lesions - Rahman, M. Sayeedur (American Society for Microbiology, 1999)
Escherichia coli cells have multiple mutagenic pathways that are induced in response to environmental and physiological stimuli. Unlike the well-investigated classical SOS response, little is known about newly recognized pathways such as the UVM (UV modulation of mutagenesis) response. In this study, we compared the contributions of the SOS and UVM pathways on mutation fixation at two representative noninstructive DNA lesions: 3,N(4)-ethenocytosine (ɛC) and abasic (AP) sites. Because both SOS and UVM responses are induced by DNA damage, and defined UVM-defective E. coli strains are not yet available, we first constructed strains in which expression of the SOS mutagenesis proteins UmuD′ and UmuC (and also RecA in some cases) is uncoupled from DNA damage by being placed under the control of a heterologous lac-derived promoter. M13 single-stranded viral DNA bearing site-specific lesions was transfected into cells induced for the SOS or UVM pathway. Survival effects were determined from transfection efficiency, and mutation fixation at the lesion was analyzed by a quantitative multiplex sequence analysis procedure. Our results suggest that induction of the SOS pathway can independently elevate mutagenesis at both lesions, whereas the UVM pathway significantly elevates mutagenesis at ɛC in an SOS-independent fashion and at AP sites in an SOS-dependent fashion. Although mutagenesis at ɛC appears to be elevated by the induction of either the SOS or the UVM pathway, the mutational specificity profiles for ɛC under SOS and UVM pathways are distinct. Interestingly, when both pathways are active, the UVM effect appears to predominate over the SOS effect on mutagenesis at ɛC, but the total mutation frequency is significantly increased over that observed when each pathway is individually induced. These observations suggest that the UVM response affects mutagenesis not only at class 2 noninstructive lesions (ɛC) but also at classical SOS-dependent (class 1) lesions such as AP sites. Our results add new layers of complexity to inducible mutagenic phenomena: DNA damage activates multiple pathways that have lesion-specific additive as well as suppressive effects on mutation fixation, and some of these pathways are not directly regulated by the SOS genetic network.